Research on the influence of cut-opening factors on flow field effect of artificial reef. (1st April 2022) - Nie, Zhaoyi; Zhu, Lixin; Xie, Wude; Zhang, Jiating; Wang, Jiahao; Jiang, Zhaoyang; Liang, Zhenlin
Abstract: Opening hole is a common choice for artificial reef design, which is still a lack of systematic research. In this article, CFD and orthogonal experimental design methods were used to study the influence of opening factors on flow field, including cut-opening ratio (OR), cut-opening interval (OI), cut-opening pattern (OP) and cut-opening shape (OS). The results showed that the OI and OP have no significant influence on the flow field effect of artificial reef, while OS and OR have significant influence. The influence of OR on the flow field effect is different with the OS, and the artificial reef with an opening hole combination of hexagonal in front and circular in side surface can have a better flow field effect. This work can provide a scientific evidence for the opening hole design of artificial reef. Highlights: The orthogonal design was used to analyze the influence of cut-opening factors. OS and OR have significant influence on the flow field effect of artificial reef, while OI and OP have no significant influence. The optimal combination of OS was studied and evaluated by the index of I r and I e . The reefs with optimized structure were favorable in water exchange.